Pengaruh Penggunaan Media Kemasan Makanan Ringan Terhadap Kemampuan Membaca Permulaan Siswa Kelas I SD Inpres Tamattia - Sri Raldiastari; Sitti Aida Azis; Sri Rahayu (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This type of research is experimental research in the form of Pre-Test Post Test Design, namely an experiment which in its implementation only involves one class as the experimental class without any comparison class (control class). The sampling technique used was a saturated sample, using the population as a sample, namely 20 students. Data collection techniques in this research used tests and observation. The data analysis used is descriptive data analysis and inferential data analysis. The results of inferential statistical analysis using the t-test formula show that the t value obtained is 10.52 with a frequency of dk = 20-1 = 19, at a significance level of 0.05, t table = 1.729. So, tcount > ttable or the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This means that the use of snack packaging media influences initial reading ability in class I Indonesian language subjects at SD Inpres Tamattia, West Bajeng District, Gowa Regency.